2019
DOI: 10.1113/jp277895
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the epithelial sodium channel in initiation of mechanically evoked swallows in anaesthetized rats

Abstract: Key points Afferents carried by the superior laryngeal nerve play a primary role in the initiation of laryngeal mechanically evoked swallows in anaesthetized rats. Amiloride and its analogues inhibit swallowing evoked by mechanical stimulation, but not swallowing evoked by chemical and electrical stimulation. The epithelial sodium channel is probably involved in the initiation of laryngeal mechanically evoked swallows. Abstract The swallowing reflex plays a critical role in airway protection. Because impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 64 publications
(113 reference statements)
0
13
1
Order By: Relevance
“…Electrical stimulation of the recurrent laryngeal nerve evokes the swallowing reflex in rats (31). We previously demonstrated that chemical and mechanical stimulation applied to the vocal folds readily induced the swallowing reflex (36). Although stable mechanical stimulation to the vocal folds was possible throughout the experiment for inducing the swallowing reflex in the present study, the size of the glottis in rats was so small that we could not precisely identify the stimulated location.…”
Section: Discussioncontrasting
confidence: 52%
“…Electrical stimulation of the recurrent laryngeal nerve evokes the swallowing reflex in rats (31). We previously demonstrated that chemical and mechanical stimulation applied to the vocal folds readily induced the swallowing reflex (36). Although stable mechanical stimulation to the vocal folds was possible throughout the experiment for inducing the swallowing reflex in the present study, the size of the glottis in rats was so small that we could not precisely identify the stimulated location.…”
Section: Discussioncontrasting
confidence: 52%
“…The swallowing reflex is easily evoked by a variety of stimulations applied to the pharyngeal and laryngeal mucosa. Some ion channels, including TRPV1, TRPA1, and TRPM8, and the epithelial sodium channel are believed to be involved in the initiation of swallowing [16,17,22]. Information is conveyed via the glossopharyngeal and/or vagus nerves to the swallowing central pattern generator (CPG) in the medulla.…”
Section: Neural Circuit For Swallowingmentioning
confidence: 99%
“…Information is conveyed via the glossopharyngeal and/or vagus nerves to the swallowing central pattern generator (CPG) in the medulla. Among the branches of the glossopharyngeal and vagus nerves, the superior laryngeal nerve (SLN) may have a primary role in initiating the swallowing refl ex [22]. The presence of a unilateral SLN lesion increased the incidence of aspiration in an infant animal model [23], and SLN afferents have important roles in facilitating laryngeal closure based on a human study [24].…”
Section: Neural Circuit For Swallowingmentioning
confidence: 99%
“…This swallowing motion stems from a constant low-frequency pumping maintained by pharyngeal muscles and bursts of high-frequency pumping from a dedicated pharyngeal nervous system (Avery and Horvitz, 1989; Raizen, Lee and Avery, 1995; Trojanowski, Raizen and Fang-Yen, 2016; Lee et al ., 2017). In mammals, the swallowing reflex is initiated when pressure receptors in the pharynx walls are stimulated by food or liquids, yet the identity of the receptor(s) that directly evoke this mechanical response remain to be identified (Tsujimura et al ., 2019). Interestingly, the Drosophila melanogaster PIEZO ortholog is a mechanosensitive ion channel (Kim et al ., 2012) required for feeding while also avoiding food over-consumption (Min et al ., 2020; Wang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%